DELAYED ERUPTION IN CLEIDOCRANIAL DYSPLASIA - Ahmed, Sanaa; Shaheen, Maria Naz; Hameed, Faisal (Journal of Ayub Medical College Abbottabad, 2020)
Cleidocranial dysplasia is a rare autosomal dominant disorder of bones mainly affecting bones formed by intra-membranous and endochondral ossification. It presents clinically as brachycephalic skull, frontal bossing, depressed nasal bridge, hypertelorism, delayed closure of fontanelles, delayed eruption of permanent teeth, missing clavicles and wide pelvis. It runs in families; sporadic cases are rarer. Just over than 1000 cases have been reported. We are presenting here 2 cases of cleidocranial dysplasia in siblings. Keywords: Cleidocranial Dysplasia; Supernumerary Tooth; Pseudarthrosis Of Clavicle; Congenital